Diagnostic analysis of potential indicators for Southwest monsoon rainfall decline in the Philippines - RAYMUND, MASANGYA (Archīum Ateneo, 2016)
Research studies on changes in the timing and intensification of the southwest monsoon (SWM) are crucial to the Philippines as SWM primarily affects the rainfall climatology of the country. Recently, Cruz et al. (2013) showed that the SWM rainfall is decr